Field Observations of Scour Behavior around an Oscillating Water Column Wave Energy Converter - Orrin Lancaster; Remo Cossu; Craig Heatherington; Scott Hunter; Tom E. Baldock (Journal of Marine Science and Engineering, 2022)
This study provides the first ever published measurements of scour and morphological change around an Oscillating Water Column (OWC) Wave Energy Converter (WEC) device at a real-world site, with the intention of informing future designs to reduce costs of the technology. A 200-kW prototype OWC WEC was deployed at King Island, Tasmania, Australia in January 2021, providing a unique opportunity to monitor the device using a combination of dive footage, multi-beam surveys and bedrock surveys. Settlement of the device was observed and monitored before ceasing once the foundation made contact with the underlying bedrock at the site. It is hypothesized that the settlement is caused by scour undermining the gravity structure’s foundations. The processes causing this scour are explored and possible future design modifications are suggested to reduce the risk of scour and settlement.